Analysis of the self-care of diabetics according to by the Summary of Diabetes Self-Care Activities Questionnaire (SDSCA) - Samuel Soares Freitas; Grazielle Roberta Freitas da Silva; Dinah Sá Rezende Neta; Ana Roberta Vilarouca Silvada (Universidade Estadual de Maringá, 2014)
This is a cross-sectional correlational study that analyzed the self-care of diabetic patients according to the SDSCA. The sample was made up by 96 people distributed into 32 health-care teams from the east/southeast region of Teresina, Piauí State. The results showed the predominance of female people, aged 70 to 79 years, education lower than 5 years, average monthly income of one minimum wage, with complications due to Diabetes (70.8%). A significant portion of the sample presented an inadequate foot care, inappropriate checking of glycemic index (92.7%), physical inactivity (63.5%), and food intake without professional monitoring (53.1%). Correlation was inversely proportional to patient educational level. In conclusion, the adherence to the treatment by these participants was unsatisfactory, showing that the need for an approach from health professionals close to their reality in order to provide them more independence and reduce the risks of complications due to Diabetes